Comparative evaluation of physical quality attributes of broiler meat under fresh and chilled conditions: Quality changes in fresh and chilled broiler meat (Bangladesh Journal of Animal Science, 2026)
The current study evaluated the impact of storage conditions after slaughter on the physicochemical characteristics of broiler breast meat, contrasting fresh carcasses assessed within 3 hours post-mortem with chilled carcasses maintained at 4 °C for 24 hours. Thirty broilers (1800 ± 50 g) were processed at the Meat Research Unit under the department of Animal Science at Bangladesh Agricultural University, and breast muscles (Pectoralis superficialis) underwent quality evaluations encompassing pH, color (L*, a*, b*), internal temperature, water-holding capacity (WHC), cooking loss, drip loss, and shear force. The findings indicated a notable decrease in pH and internal temperature in chilled meat when contrasted with fresh samples (p < 0.001), highlighting the usual post-mortem glycolytic acidification and thermal reduction processes. Chilled meat exhibited markedly reduced shear force values (p < 0.001), indicating enhanced tenderness after rigor resolution. The cooking loss was significantly higher in fresh samples (p = 0.004), while chilled meat demonstrated enhanced water-holding capacity (WHC) (p < 0.001). The color values exhibited slight differences across treatments, with no notable effects detected for L* and a*. However, the chilled meat displayed a minor decrease in yellowness (b*, p = 0.048). The reduction in drip loss was significantly greater in chilled samples (p < 0.001), underscoring improved moisture retention throughout the storage period. In summary, chilled broiler breast meat demonstrated favorable textural and functional attributes while preserving visual appeal, indicating that brief chilling is an advantageous post-slaughter method for boosting meat tenderness, ensuring color stability, and enhancing processing yield. The results indicate a strong inclination within the industry towards chilled poultry meat, positioning it as a superior option compared to the immediate post-slaughter sale of fresh meat.Bangladesh Journal of Animal Science 54 (4): 74-80, 2025